1985
DOI: 10.1002/clc.4960080304
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the electrocardiographically estimated infarct size and 1 ‐ and 2‐year survival in acute myocardial infarction

Abstract: Summary:In 587 patients with acute myocardial infarction (AMI) and no previous MI, electrocardiographically estimated infarct size was related to 1-and 2-year mortality. The overall mortality was higher in patients with transmural MI (Q-or R-wave changes in standard ECG) than in patients with subendocardial infarction (ST-Twave changes in standard ECG) after 1 year (18.8% compared to 6.5% p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…, 1984b) but have a lower incidence of angina pectoris during follow-up (Cannom et a f . , 1976;Herlitz et al, 1985). Not surprisingly, patients with possible infarction had less signs of congestive heart failure during initial hospitalization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, 1984b) but have a lower incidence of angina pectoris during follow-up (Cannom et a f . , 1976;Herlitz et al, 1985). Not surprisingly, patients with possible infarction had less signs of congestive heart failure during initial hospitalization.…”
Section: Discussionmentioning
confidence: 97%
“…During the last decade there has been a debate as to whether different types of infarctions have a different prognosis (Cannom et al, 1976;Herlitz et al, 1984a;Thanavaro et al, 1980) and a different morbidity pattern (Cannom et al, 1976;Herlitz et al, 1985). There have also been studies comparing the outcome of patients who turned out to have no confirmed infarction with the outcome of those who had a confirmed infarction (Hovendahl 1971;Moms et al, 1983;Schroeder et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic Q waves are related to the size of the MI [8,9]. Large MIs which involve more than 10% of the ventricular myocardium often exhibit significant Q waves, while small infarcts may occur without leaving residual pathologic Q waves on electrocardiogram [10].…”
Section: Discussionmentioning
confidence: 99%